Introduction to Corrections - Roberson, Cliff (Copperhouse Pub., 2003)
Thoroughly updated to reflect recent developments in corrections, INTRODUCTION TO CORRECTIONS, Second Edition provides a concise, yet comprehensive overview of the American correctional system that considers all types of custody, including probation and parole. The text is written for an introductory corrections course that focuses on both adult corrections and juvenile court dispositions. A new co-author, Michael Birzer, brings his teaching experience and insight to the second edition. Cliff Roberson's experiences as a judge, prosecutor, and defense counsel, coupled with his lengthy college teaching experience, add unique depth to his understanding of the field. With these authors as their guides, readers will attain a practical and complete understanding of the correctional system in an interesting and thought-provoking way